Werwolf! : the history of the National Socialist guerrilla movement, 1944-1946 - Biddiscombe, Alexander Perry, 1959- (University of Toronto Press, 1998)
Near the end of the Second World War, a National Socialist resistance movement, known as the Werwolf, flickered briefly to life in Germany and its borderlands. Dedicated to delaying the advance of the Allies on both fronts, the Werwolf succeeded in scattered acts of sabotage and violence. By the spring of 1945, it also showed signs of becoming a vengeful Nazi reaction against the German populace itself. 'Collaborators' and 'defeatists' were frequently assassinated, and crude posters warned that certain death would follow any failure to resist the enemy. Werwolf violence failed to mobilize a spirit of national resistance. Biddiscombe argues that the group was poorly led, armed, and organized, and that it was doomed to failure given the war-weariness of the populace and the hesitancy of young Germans to sacrifice themselves on the funeral pyre of the regime. He also demonstrates that although the group failed to assume a popular character, its influence was still great and its revolutionary sentiments would have grave implications for the future. Werwolf! is the most complete history to date of the Nazi partisan movement. It will be of great interest to general readers as well as to military historians.